1998
DOI: 10.1212/wnl.51.2.526
|View full text |Cite
|
Sign up to set email alerts
|

Sleep-related violence, injury, and REM sleep behavior disorder in Parkinson's disease

Abstract: PD patients with SRI frequently have behavioral features of RBD. If RBD underlies most SRI, treatment with appropriate pharmacologic agents, such as clonazepam, may prevent future occurrences of SRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
156
0
7

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 350 publications
(172 citation statements)
references
References 8 publications
9
156
0
7
Order By: Relevance
“…As a matter of fact, this questionnaire has never been validated in PD patients. The frequency of RBD in PD, as diagnosed by questionnaires, is different from video-polysomnographically diagnosed RBD (its frequency ranges from 33-47%), demonstrating the difficulty to predict RBD clinically [14,28,29]. It should be noted, however, that in a recent Japanese study, 54% of PD patients studied were diagnosed with RBD, based on questionnaire data [30].…”
Section: Sleepwalking and Parkinson's Disease: Prevalencementioning
confidence: 85%
See 1 more Smart Citation
“…As a matter of fact, this questionnaire has never been validated in PD patients. The frequency of RBD in PD, as diagnosed by questionnaires, is different from video-polysomnographically diagnosed RBD (its frequency ranges from 33-47%), demonstrating the difficulty to predict RBD clinically [14,28,29]. It should be noted, however, that in a recent Japanese study, 54% of PD patients studied were diagnosed with RBD, based on questionnaire data [30].…”
Section: Sleepwalking and Parkinson's Disease: Prevalencementioning
confidence: 85%
“…In questionnaire-based studies asking for sleepwalking/nighttime wandering in PD patients, frequencies ranging from 2% (4/201) [13], 3% (2/61, resp. 2/66) [9,14] to 5% (16/303) [15] can be found in the literature, however, no detailed characteristics of the phenomenon were studied. The aim of the present study was to assess frequency and characteristics of SW/nighttime wandering in patients with PD.…”
Section: Introductionmentioning
confidence: 99%
“…There is a high occurrence of RBD in patients with PD, up to 60% in some studies [57,58], and up to 80% in DLB patients [59] [60][61][62], with Postuma et al [61] also finding deficits in color discrimination compared with a control population. Using questionnaires, they also found autonomic dysfunction with abnormalities in constipation, erectile dysfunction, and urinary scores [61].…”
Section: While Sleep Disorders Worsen As Pd Advances It Is Clear Thamentioning
confidence: 97%
“…2 Most patients report vivid, frightening dreams, leading to violent behavior, often resulting in injuries of patients or their bed partners. 3 The prevalence of RBD reported in the general population is < 1%, 4,5 whereas in neurodegenerative disorders, especially synucleinopathies such as Parkinson's disease (PD), dementia with Lewy bodies (DLB), and multiple system atrophy (MSA), a much higher frequency is found. 6,7 It has been shown that PSG is the gold standard for the diagnosis of RBD, since only half of the patients are detected by history.…”
Section: S C I E N T I F I C I N V E S T I G a T I O N Smentioning
confidence: 99%